Metropolitan Research (transcript Verlag, 2022)
Metropolitan research requires multidisciplinary perspectives in order to do justice to the complexities of metropolitan regions. This volume provides a scholarly and accessible overview of key methods and approaches in metropolitan research from a uniquely broad range of disciplines including architectural history, art history, heritage conservation, literary and cultural studies, spatial planning and planning theory, geoinformatics, urban sociology, economic geography, operations research, technology studies, transport planning, aquatic ecosystems research and urban epidemiology. It is this scope of disciplinary - and increasingly also interdisciplinary - approaches that allows metropolitan research to address recent societal challenges of urban life, such as mobility, health, diversity or sustainability.